Variation in Macrophage Phagocytosis of Streptococcus agalactiae Does Not Reflect Bacterial Capsular Serotype, Multilocus Sequence Type or Association with Invasive Infection - Lisa M. Rogers; Jennifer A. Gaddy; Shannon D. Manning; David M. Aronoff (Case Western Reserve University, 2018)
Background: Group B Streptococcus(GBS) is an encapsulated Gram-positive coccus that is an important cause of infections in adults with chronic medical conditions, pregnant women, and neonates. GBS causes a range of clinical syndromes, from asymptomatic colonization to deep-seated invasive and highly lethal infections. Macrophages are important sentinels of innate immunity, protecting host tissues from infection when bacteria advance beyond cutaneous or mucosal barriers. We hypothesized that the capacity for macrophages to phagocytose unopsonized GBS would vary across distinct clinical strains, and such differences would reflect serotype diversity. Methods: A high-throughput screen using the phorbol ester-differentiated THP-1 macrophage-like human cell line was used to quantify phagocytosis of a diverse group of 35 different human clinical isolates of GBS representing a wide variety of capsular serotypes. Validation studies were conducted using human primary phagocytes. Results: Phagocytosis of GBS differed widely across clinical isolates but this was not related to capsular serotype, genetic sequence type, pilus type, or clinical source of the GBS isolate (colonizing or invasive strain). Conclusions: Structural and/or biochemical differences among diverse GBS strains are reflected in a diverse capacity for macrophages to ingest them through non-opsonic phagocytosis. Mechanisms explaining these differences are not clear. Keywords: Neonatal sepsis; innate immunity; macrophages; Gram-positive bacteria; diabetes